Overview of a compiler for synthesizing MATLAB programs onto FPGAs. - Banerjee, P. (IEEE Transactions on VLSI systems)
This paper describes a behavioral synthesis tool called AccelFPGA which reads in high-level descriptions of digital signal processing (DSP) applications written in MATLAB, and automatically generates synthesizable register transfer level (RTL) models and simulation testbenches in VHDL or Verilog. The RTL models can be synthesized using commercial logic synthesis tools and place and route tools onto field-programmable gate arrays (FPGAs). This paper describes how powerful directives are used to provide high-level architectural tradeoffs for the DSP designer. Experimental results are reported on a set of eight MATLAB benchmarks that are mapped onto the Xilinx Virtex II and Altera Stratix FPGAs.